Tarlac City Local Studies Center inducing communal learning through reintegrative redevelopment of the urban streets and city block - Zarraga, Rico Antonio R. (College of Architecture, University of the Philippines Diliman, 2020)
Many historical cities have started deteriorating due to improper planning and the lack of political will to preserve its local identity. Urban growth centers have directed their development approaches towards profit-centric policies which constantly eats up the cultural and historical essence of the area, manifesting itself with unequal economic growth, demolition of historical structures, and displacement of locals to accommodate income generating establishments. The Poblacion of Tarlac is identified as the site of the future Central Business District of the province, a city so eager for development yet continues to neglect its rich historical background. Minimal efforts are done to preserve it and the condition continues to worsen with constant migration of locals, clearing operation of vendors, and demolition of many historical structures, all in the name of "progress." The study aims to introduce a framework on how to promote physical and socio-economic development by bridging the social, cultural, and economic facets of a locale. Architecture as a bridging factor towards a city's approach to induce communal learning within and outside the community. The study utilized existing urban elements within the site to develop and explored the potential of multiple space characteristics to become social spaces. The resulting architecture serves as a context-dependent example of how we can develop our urban spaces, enriching experiences, promoting local culture while ultimately reintegrating the value back to the community.